Rock mechanics study on block caving design following open pit mining: a case study of Yandong copper mine - Zanmin, X; Yuming, L; Mingchun,L; Wen, L; Xiaolong, L; Pengzhao, R; Changnian, X (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
The application of open pit and block caving combined (OPBC) mining is an extremely challenging task, particularly under complex orebody occurrence conditions. For thick, low-grade deposits with shallow to medium orebody depths, OPBC represents the most economical mining method. Taking the Yandong copper mine as the engineering background, this study is a rock mechanics study on the applicability of OPBC and demonstrates a stepwise methodology for the assessment and safe recovery of OPBC method at the Yandong copper deposit, including the determination of open pit slope angle and mining depth, investigation of ore-rock mass structure, caveability evaluation and simulation analysis of progressive failure of the open pit slope during underground mining using Flac3D. The study demonstrates that implementing OPBC at the Yandong copper mine is feasible under the evaluated geological conditions, and the results can serve as a reference for the design of similar mines.
Keywords: open pit and block caving combined mining; caveability evaluation; progressive failure; caving-induced subsidence; mine design